PENGARUH KARIR DAN KOMPENSASI GAJI TERHADAP MOTIVASI KERJA KARYAWAN HYPERMART CIPUTRA SERAYA PEKANBARU - Putri Clawson; Sherly Mardiansus (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2015)
ABSTRACT The purpose of this study was to determine how the effect of compensation on employee work motivation on Ciputra Seraya Hypermart Pekanbaru. The method used in this study is a qualitative study using statistical analysis tools and service solutions (SPSS) version 17.0. In general, the results of testing the validity and reliability of research question items have given good results. Hypothesis test results (H1) partially in this study indicate that the value of tcount is 4.613, while ttable is 2.052, where tcount is 4.613> ttable 2.052, with a significant level of 0.000 being lower at α = 0.05 This shows that the hypothesis (H1 ) accepted, where the salary variable has a significant and positive effect on employee work motivation. Hypothesis test results (H2) partially in this study indicate that the value of tcount is 0.502, while ttable is 2.052, where tcount is 0.502 <ttable 2.502, with a significant level of 0.619 being higher at α = 0.05. The second hypothesis (H2) proposed in this study was rejected, where career variables did not affect employee work motivation.